Systems with Fractional Variable-Order Difference Operator of Convolution Type and Its Stability - Mozyrska, Dorota; Wyrwas, Malgorzata (Elektronika ir Elektrotechnika, 2018)
In the paper the Grünwald–Letnikov-type linear fractional variable order discrete-time systems are studied. The conditions for stability and instability are formulated. The regions of the systems stability are determined accordingly to locus of eigenvalues of a matrix associated to the considered system. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21846